2012
DOI: 10.1111/j.1476-5381.2012.01863.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological dissection of Kv7.1 channels in systemic and pulmonary arteries

Abstract: BACKGROUND AND PURPOSEThe aim of this study was to characterize the functional impact of KCNQ1-encoded voltage-dependent potassium channels (Kv7.1) in the vasculature. EXPERIMENTAL APPROACHMesenteric arteries, intrapulmonary arteries and thoracic aortae were isolated from adult rats. Kv7.1 channel expression was established by fluorescence immunocytochemistry. Wire myography determined functionality of these channels in response to selective blockers and activators. Xenopus oocytes expressing Kv7.1 channels we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
61
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(62 citation statements)
references
References 33 publications
1
61
0
Order By: Relevance
“…Similar to previous work, [4][5][6]14 we found that LAD coronary arteries from SHRs exhibited considerably less K V 7.4 protein compared with arteries from Concentration-dependent effect curve of K V 7 inhibitor XE-991 and linopirdine (C) in NT and spontaneously HT rats on arterial tone. Data are mean±SEM.…”
Section: K V 7 and Kcne Expression In Rat Coronary Arteriessupporting
confidence: 77%
See 3 more Smart Citations
“…Similar to previous work, [4][5][6]14 we found that LAD coronary arteries from SHRs exhibited considerably less K V 7.4 protein compared with arteries from Concentration-dependent effect curve of K V 7 inhibitor XE-991 and linopirdine (C) in NT and spontaneously HT rats on arterial tone. Data are mean±SEM.…”
Section: K V 7 and Kcne Expression In Rat Coronary Arteriessupporting
confidence: 77%
“…In addition, it shows that structurally different K V 7.2 to 7.5 activators ((S)-1, BMS-254352, and retigabine) are effective relaxants of precontracted coronary arteries at all orders of artery, whereas the K V 7.1 activator R-L3 has no relaxant effect at concentrations where it relaxes mesenteric and pulmonary arteries. 4 Importantly, the relaxant effect of the K V 7.2 to 7.5 activators was markedly impaired in coronary arteries from SHRs similar to findings in aorta, mesenteric and renal arteries, 6,14 which was associated with a reduction in K V 7.4 protein abundance. In contrast to the rat aorta, 6 there was no change in KCNQ expression in the coronary arteries or mesenteric arteries (also observed in gracilis muscle arteries from SHRs).…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…In contrast, the Kv7.1-selective activator, R-L3, was an ineffective relaxant of MCAs ( Figure 1B) at concentrations that produced relaxations of other arteries. 12 Cumulative application of 5-HT concentrations evoked robust contractions of MCAs ( Figure 1C). The inhibition of Kv7 channels by linopirdine (1 μmol/L; n=4) caused a moderate enhancement in 5-HT responses.…”
Section: Resultsmentioning
confidence: 99%